17.6k views
1 vote
Plz help me thanks so mycghh​

Plz help me thanks so mycghh​-example-1
User Kzfabi
by
5.8k points

1 Answer

3 votes

Answer:

(4). g(2) > f(2) False

Explanation:

(1). (f(0) = 2) > (g(0) = - 4) (True)

(2). f( - 4) = 4( - 4 ) + 2 = - 14

g( - 4) = (5/2)(- 4) - 4 = = - 14

f( - 4) = g( - 4) (True)

(3). f(6) = 4(6) + 2 = 26

g(12) = (5/2)(12) - 4 = 26

f(6) = g(12) (True)

(4). g(2) = (5/2)(2) - 4 = 1

f(2) = 4(2) + 2 = 10

g(2) > f(2) (False)

User Daniel De Zwaan
by
6.4k points